2020
DOI: 10.1088/1742-6596/1613/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of secondary school mathematics teachers’ pedagogical content knowledge and intended teaching in curriculum reformation

Abstract: This study was conducted in response to the curriculum reform in Indonesia which have encouraged a different approach to teach the mathematics content employing innovative methodology or model in teaching and learning. This study aimed to understand the secondary school mathematics teachers’ Pedagogical Content Knowledge (PCK) towards curriculum reformation. Every participant was interviewed in relation to the domain of PCK, and some intended teaching practice in K-13. The result shows that each teacher has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In Malang City, teachers exhibited resilience in implementing K-13, engaging in training, forming lesson study groups, and undertaking clinical supervision to adapt to the curriculum's scientific approach (Gunawan, 2017). Teachers simplified complex concepts to give students real-life examples (Hidayat & Setyawan, 2020). In Bandung, they developed innovative learning implementation plans and monitored student progress with methods like "star" stickers for positive reinforcement (Rusman, 2015).…”
Section: Teachers' Practice Resilience and Innovativementioning
confidence: 99%
See 1 more Smart Citation
“…In Malang City, teachers exhibited resilience in implementing K-13, engaging in training, forming lesson study groups, and undertaking clinical supervision to adapt to the curriculum's scientific approach (Gunawan, 2017). Teachers simplified complex concepts to give students real-life examples (Hidayat & Setyawan, 2020). In Bandung, they developed innovative learning implementation plans and monitored student progress with methods like "star" stickers for positive reinforcement (Rusman, 2015).…”
Section: Teachers' Practice Resilience and Innovativementioning
confidence: 99%
“…Internally, teachers' personal beliefs about students' inability to adapt to new teaching and their comfort with familiar teacher-centered methods significantly influence this reversion (Basalama, 2010;Diem, 2016). Limited skills in student-centered techniques, interactive discussion, and the integration of new methods like inquiry-based contribute to their reliance on traditional methods (Diem, 2016;Pratiwi et al, 2020;Hidayat & Setyawan, 2020).…”
Section: Teachers' Practice Resilience and Innovativementioning
confidence: 99%
“…The results of the study detailing professional development showed a good effect on PCK. For instance, professional development programs (Ekmekci et al, 2019;Hidayat & Setyawan, 2020;Maboya et al, 2022;Sarkim, 2020), content-focused professional development (Richter et al, 2021), model/ professional training/ teacher training/ collaboration programs (Gambini & Lenart, 2021;Jeschke et al, 2021;Kurt-Birel et al, 2020;Manderfeld & Siller, 2019;Saputra et al, 2019;Sunzuma & Maharaj, 2019;Tang, 2018;Yildiz & Akyuz, 2019;Yilmaz & Demir, 2021), seminar/ workshops/ in-service training (Ansah et al, 2020;Chang et al, 2020;Kurt-Birel et al, 2020;Moh' d et al, 2021), educational course/ pedagogy course (Lau, 2019;Lee et al, 2018), school based continuous professional development/ on-site professional training (lesson study) (Helmbold et al, 2021;Mhakure, 2019), structured interventions/ professional learning workshops (Hilton & Hilton, 2018), regular meetings (Taylan et al, 2022), microteaching course/ microteaching/ teaching practicums (Setyaningrum et al, 2018) and a two-week summer institute (Schoen et al, 2019) were implemented to enhance mathematics teachers' PCK level effectively. Notably, terms such as model, professional training, teacher training and collaboration program were frequently used to represent professional development in most of the studies.…”
Section: Professional Developmentmentioning
confidence: 99%
“…In our research, we focused on teachers' knowledge in implementing cooperative learning. Teachers who master content knowledge tend to choose a suitable teaching approach easily [21]. Content knowledge refers to teachers' knowledge of subject matters that need to be mastered by teachers and learned by pupils.…”
Section: Introductionmentioning
confidence: 99%